Inserting pedicle screws in lumbar spondylolisthesis – The easy bone conserving way - Lal, Hitesh (J Clin Orthop Trauma, 2017)
BACKGROUND: Pedicle screw fixation in high grade lumbar listhetic vertebral body has been nightmare for Orthopaedic and spine surgeons. This is because of abnormally positioned listhetic pedicles and non-visualization of pedicle in conventional image intensifier (C-Arm). This results into increased surgical time, more blood loss, radiation exposure and more chances of infection. To overcome this problem, we have devised a new Technique of putting of pedicle screw fixation in listhetic vertebrae. METHODS: Total 20 patients of average age of 42 (25–56) were included during 2010 to 2015. Listhesis was classified according to etiology, Meyerding grading and DeWald modification of Newman criteria used for assessment of severity for spondylolisthesis on standing X-ray lumbosacral spine. Patients satisfying following criteria were considered for surgery. Age more than 20 years, with single involvement of either L4-5/L5-S1, high grade spondylolisthesis (≥ 50% Meyerding grade), unresolving radiculopathy, cauda equina syndrome or pain with and without instability not relieved by 6 months of conservative treatment. According to Meyerding radiographic grading system,10 patients were of type II and 8 of type III and 2 of type IV. Treatment given was pedicle screw fixation, reduction of listhesis vertebra and spinal fusion with our technique. PLT was done in 10 cases and transforaminal lumbar interbody fusion (TLIF) in the other 10 cases. RESULTS: Mean follow up duration was 2 years (range 1.3–3.3 year). The average preoperative LBP VAS of low back pain were 6.7 and average LP VAS for leg pain 5.7. Postoperatively at final follow up there was reduction of LBP VAS to 2.2 and LP VAS to 0.5. There was rapid reduction in their LBP VAS in first two visits at 4 weeks and in LP VAS in first three visits at 8 weeks. The pain-free walking distance improved significantly. The average pre-operative ODI score was 51.4, improved to 18.6 postoperatively. There was no difference in above scores between PLT and TLIF. CONCLUSION: Our surgical technique used for high grade spondylolisthesis is safe, cost-effective, bone-preserving, reliable, and reproducible for high grade Lumber spondylolisthesis.